Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203449974
Keywords: approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires

Garçon manqué - Bouraoui, Nina (Librairie générale française, 2000)
Dans les années 70, la guerre d'Algérie est encore dans tous les esprits. Ce récit autobiographique décrit la difficulté de vivre en Algérie avec une mère française, et de vivre en France avec un père algérien
Section: 188 pages ; 18 cm
Keywords: 1900-1999; 1970-1979; afrique; afrique du nord; algérie; approches et analyses; arts; cours; discipline; europe; france; lit2815; premier cycle; périodes historiques; racisme; roman; régions géographiques; système colonial; systèmes d'oppressions; études littéraires

L'événement - Ernaux, Annie (Gallimard, 2000)
L'occasion d'un banal examen dans un cabinet médical replonge la narratrice plus de trente ans en arrière, en janvier 1964, au moment de son avortement clandestin.
Section: 114 pages ; 19 cm.
Keywords: 1900-1999; arts; autobiographie; avortement; cours; discipline; europe; france; justice reproductive; lit2815; lit3220; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Genders - Glover, David; Kaplan, Cora (Routledge, 2000)
"Gender" has, in recent years, become one of the busiest terms in literary and cultural theory, as well as being one of the most contested. David Glover and Cora Kaplan chart the main lines of contemporary debate surrounding gender in a guide which:* presents a history of the term, from the sexology of psychoanalysis of the 1960s to its current usage within the interdisciplinary field of gender studies* looks at the major perspectives on gender from second-wave feminist writers and critics* examines new work on masculinity in literary and cultural studies* assesses how the creation of new queer and gendered identities has impacted the study of literature* surveys empirical and theoretical work on readership and spectatorship, looking in detail at modes of fantasy, cultural consumption, reader response and fan cultures.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; antiféminisme; approches et analyses; cours; culture populaire; discipline; fem1000; littérature; masculinisme; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; états-unis; études culturelles; études littéraires

Coming Out of the Castle: Gothic, Sexuality and the Limits of Language - Grove, Allen W. (Historical Reflections / Réflexions Historiques, 2000)
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; histoire; histoire et politique; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; thématiques; études littéraires